Shared Decision Making for the Emergency Provider: Engaging Patients When Seconds Count - Hemal K. Kanzaria (Association of American Medical Colleges, 2020)
Introduction Physicians need to be able to communicate the myriad of management options clearly to patients and engage them in their health care decisions, even in the fast-paced environment of the emergency department. Shared decision making (SDM) is an effective communication strategy for physicians to share diagnostic uncertainty, avoid potentially harmful tests, and solicit patients' preferences for their care. Role-playing with just-in-time feedback is an effective method to learn and practice SDM before having these conversations with patients. Methods This flipped classroom workshop featured precourse materials and an in-class session incorporating a short lecture outlining a framework for SDM, followed by role-playing through patient scenarios. Learners took turns playing the physician or patient role and received feedback on their communication skills while in the physician role. A faculty examiner subsequently assessed skill attainment using a simulated patient encounter and checklist of critical actions. Results The workshop was an interactive and effective way to teach SDM to 28 PGY 1 and PGY 2 emergency medicine residents. Two months after attending the workshop, over 75% of the first-year residents were able to complete all the elements of the SDM process in a simulated patient encounter; four residents required no prompting by the examiner. Discussion A communications workshop that incorporates role-playing with different patient encounters is an interactive way to teach SDM for the emergency setting. Residents early in their clinical training can benefit from learning and practicing SDM in a simulated setting.